EVALUATION OF IN VITRO ANTIOXIDANT PROFILE OF SELECTED CEREALS - SINGH ALKA; YADAV NEELAM; SHARMA SHRUTI (International Journal of Pharma and Bio Sciences, 2013)
The antioxidant activities, total phenolic content (TPC) and total flavonoid content (TFC) of seven selected cereals including Wheat (Triticum aestivum var WH-147), Rice (Oryza sativa var Ganga Kaveri), Basmati rice (Oryza sativa var Pusa-1121), Maize (Zea mays var K-65), Pearl millet (Pennisetum americanum var Banjara Gold), Barley (Hordeum vulgare var Ratna ) and Sorghum (Sorghum bicolor var MFSH-4 ) were determined. The TPC was determined according to the folin-ciocalteu method and TFC by spectrophotometric method. TPC and TFC varied from 53.5 to 211.2 mg/100g and 0.28 to 0.65 mg QE/g respectively. Antioxidant activity of methanolic extract of cereals was evaluated according to the DPPH radical scavenging activity. Antioxidant activity, reducing capacity and Ferric reducing antioxidant potential (FRAP) ranged from 63.9 to 73 %, 18.6 to 62 AAE/g and 1.70 to 3.70 mmoL of Fe equi/g of flour respectively.